2021
DOI: 10.3389/fpsyg.2021.663799
|View full text |Cite
|
Sign up to set email alerts
|

Forced Social Isolation and Mental Health: A Study on 1,006 Italians Under COVID-19 Lockdown

Abstract: Most countries have been struggling with the spread of the COVID-19 pandemic imposing social isolation on their citizens. However, this measure carried risks for people's mental health. This study evaluated the psychological repercussions of objective isolation in 1,006 Italians during the first, especially strict, lockdown in spring 2020. Although varying for the regional spread-rate of the contagion, results showed that the longer the isolation and the less adequate the physical space where people were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
188
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(203 citation statements)
references
References 38 publications
(52 reference statements)
7
188
0
8
Order By: Relevance
“…Factors associated with higher levels of distress among those who have been quarantined for other reasons (such as exposed healthcare professionals) include fears of infection and stigma, anger and boredom, frustration with inadequate information, financial loss 9 , 18 and length of quarantine. 9 , 10 Some researchers have focused on beliefs and attitudes as factors associated with mental health distress among those in quarantine. For instance, survey research in Italy has found that those in regions with lower COVID-19 contagion rates reported higher levels of quarantine distress than those in high contagion areas, a finding that the researchers attributed to a sense of justice or proportionality.…”
Section: Mental Health and Covidmentioning
confidence: 99%
“…Factors associated with higher levels of distress among those who have been quarantined for other reasons (such as exposed healthcare professionals) include fears of infection and stigma, anger and boredom, frustration with inadequate information, financial loss 9 , 18 and length of quarantine. 9 , 10 Some researchers have focused on beliefs and attitudes as factors associated with mental health distress among those in quarantine. For instance, survey research in Italy has found that those in regions with lower COVID-19 contagion rates reported higher levels of quarantine distress than those in high contagion areas, a finding that the researchers attributed to a sense of justice or proportionality.…”
Section: Mental Health and Covidmentioning
confidence: 99%
“…These psychosocial changes were consistent with the score of Wuhan residents and the impressions reported by the media. Another study about the social isolation in Italy showed that longer isolation could increase people's mental stress ( 20 ). Government needs to take these factors into account when they implement social distancing policies and provide adequate online mental support for people in need.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of the lockdown were studied on 1,006 Italians and showed that "the longer the isolation and the less adequate the physical space where people were isolated, the worse the mental health (e.g., depression)." 2 Through experiencing this challenging way of living in lockdown, we learn to value specific architectural, social and environmental aspects of living. This research focusses on the following.…”
Section: Rethinking the Traditional Housementioning
confidence: 99%
“…First and foremost, 'The Rhodo Workhome' is designed in response to social isolation amongst home-based workers and loneliness amongst singles in lockdown. This social isolation which is occurring in lockdown, is argued in 'A Study on 1,006 Italians Under COVID-19 Lockdown' 4 and goes hand in hand with working from home. Frances Holliss, architect and Doctor of philosophy in the field of 'The architecture of home-based work', states in her doctoral research that there is a "blindness to homebased work and its social and spatial consequences 5 ".…”
Section: Social Isolation Of Both Singles and People Working From Homementioning
confidence: 99%